2009
DOI: 10.1590/s0102-311x2009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of emergency services: a systematic review of prevalence and associated factors

Abstract: This systematic review aimed to measure the prevalence of inappropriate emergency department (ED) use by adults and associated factors. The review included 31 articles published in the last 12 years. Prevalence of inappropriate ED use varied from 20 to 40% and was associated with age and income. Female patients, those without co-morbidities, without a regular physician, without a regular source of care, and those not referred to the ED by a physician also showed more inappropriate ED use, with the relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
257
5
43

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(321 citation statements)
references
References 43 publications
16
257
5
43
Order By: Relevance
“…42,43 A reduction in ED utilization for sick visits of close to 30% would therefore represent a significant cost savings. Furthermore, our data demonstrated that preadolescents, who are more likely to have inappropriate ED utilization than adolescents or adults, 44 may benefit the ARTICLE most from having a medical home. Thus, although further studies are needed, promoting the medical home among children without special health care needs presents a promising avenue for additional cost savings and improved health.…”
Section: Discussionmentioning
confidence: 63%
“…42,43 A reduction in ED utilization for sick visits of close to 30% would therefore represent a significant cost savings. Furthermore, our data demonstrated that preadolescents, who are more likely to have inappropriate ED utilization than adolescents or adults, 44 may benefit the ARTICLE most from having a medical home. Thus, although further studies are needed, promoting the medical home among children without special health care needs presents a promising avenue for additional cost savings and improved health.…”
Section: Discussionmentioning
confidence: 63%
“…The prevalence of inappropriate ED use, if appropriate use is defined as presenting with a medical condition that could only be assessed in the ED, varies from 20% to 40%. 24,25 Reasons for choosing to visit the ED are lack of awareness of other facilities, perceived seriousness of the condition, trust in the ED staff and proximity to the ED. 25 Patients with inappropriate PED visits due to the lack of Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of using tools for family, individual and social risk classification to improve dental care in these sectors and prevent emergency situations 18 . Therefore access to primary care eases the burden of dental emergency provided the care of emergency in time and in an opportune manner is guaranteed 19 .…”
Section: Discussionmentioning
confidence: 99%